O ensino da saúde coletiva em instituições de ensino superior do Espírito Santo, Brasil (Brazilian Journal of Health Research, 2022)
Introduction: The teaching of Collective Health is fundamental for the formation of qualified health professionals to work in the Unified Health System. However, there are few studies that analyze the real situation of Public Health teaching by the Higher Education Institutions. In addition, the few existing studies demonstrate that the teaching of Public Health in Brazil has little curricular structure and lack of content on public policies. Objective: To analyse the distribution of Public Health disciplines in higher education institutions of Espírito Santo. Methods: It is a descriptive study developed based on a documentary survey through the Ministry of Education’s online portal and on the websites of higher education institutions located in Espírito Santo that offered at least one course in the health area. Data were entered into a contingency table and analyzed using descriptive statistics. Results: 68 courses in the health area from 10 high education institutions (one public and nine private) were analyzed. Public health offers between 1 and 3 subjects, corresponding between 1% to 5% of the general subjects of the courses and 1% to 3% of the total workload. However, courses such as Medicine and Occupational Therapy have the highest workloads in public health education. Conclusion: Public health education in the region is offered in few subjects, representing low percentages in the curriculum.
Keywords: Public Health; Education; Higher Education Institutions